P89 Patient reported comorbidity is not a reliable data source: a systematic review of the literature. (8th April 2021) - Lin, Chung Mun Alice; Orman, Alexander; Clement, Nicholas D; Deehan, David J; Lin, Chung M A
Abstract: Introduction: There is currently an increased demand for elective orthopaedic surgery. However, due to the ever-growing financial, time and resource limitations, there is a pressing need to identify those who would benefit most from surgery but with the lowest risk of complications. Comorbidities are a fundamental factor in this decision and the traditional way to ascertain this is through medical record data abstraction during pre-operative assessment. However, this can be time consuming and expensive. We therefore set out to establish whether patient reported comorbidities are reliable as a principal source of information. Method: Searches were performed on PubMed and Medline, and citations independently screened. Included studies were published between 2010 to 2020 assessing the reliability of at least one patient reported comorbidity against their medical record or clinical assessment as gold standard. Cohen's kappa coefficient values were grouped into systems and a meta-analysis performed comparing the reliability between studies. Results: Meta-analysis data showed poor-to-moderate reliability for diseases in cardiovascular, musculoskeletal, neurological and respiratory systems as well as for malignancy and depression. Endocrine diseases showed good-to-excellent reliability. Factors found to affect the concordance included sex, age, ethnicity, education, living alone, marital status, number or severity of comorbidities, mental health and disability. Conclusion: Our study showed poor-to-moderate reliability for all systems except endocrine, consisting of thyroid disease and diabetes mellitus, which demonstrated good-to-excellent reliability. Although patient reported data is useful and can facilitate a complete pre-operative overview of the patient, it is not reliable enough to be used as a standalone measure.